2012
DOI: 10.1007/s11832-012-0449-4
|View full text |Cite
|
Sign up to set email alerts
|

The talar axis–first metatarsal base angle in CVT treatment: A comparison of idiopathic and non-idiopathic cases treated with the Dobbs method

Abstract: Purpose Congenital vertical talus (CVT) appears as an idiopathic or non-idiopathic deformity. In this study, we analysed the talar axis-first metatarsal base angle (TAM-BA) values of idiopathic and non-idiopathic CVT cases treated with the Dobbs method. Materials and methods Between January 2007 and July 2012, 20 cases of CVT were treated, starting with a manipulation, casting and a minimally invasive surgical approach. We analysed retrospectively the TAMBA values in idiopathic and non-idiopathic CVT. As a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 16 publications
3
21
1
1
Order By: Relevance
“…Of note, the study which reported no recurrence had a very short follow-up time. Four of the te teratological feet had recurrence, which is lower than other reports of up to 66.7 % recurrence in the teratological group [ 14 , 26 ]. There was no significant difference between the rate of recurrence between the teratological and idiopathic patients.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Of note, the study which reported no recurrence had a very short follow-up time. Four of the te teratological feet had recurrence, which is lower than other reports of up to 66.7 % recurrence in the teratological group [ 14 , 26 ]. There was no significant difference between the rate of recurrence between the teratological and idiopathic patients.…”
Section: Discussioncontrasting
confidence: 69%
“…They found the talar axis-first metatarsal angle to be significantly smaller in the unsuccessfully treated group compared with those who were successfully treated ( p < 0.0001). The authors found that the flexibility of the talonavicular joint could be a predictor of success in minimally invasive treatment [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some of the more rigid non-isolated vertical tali in which serial casting does not achieve full correction, then a selective capsulotomy of the anterior subtalar joint completes the correction 10 . Following the first description of this minimally invasive method for the treatment of congenital vertical talus 17,18 , many centers replicated a high success rate for achieving initial clinical and radiographic correction for both isolated and non-isolated vertical tali 10,[19][20][21][22][23][24][25][26]32 . However, the follow-up was less than two years in those studies, and none had a comparison cohort treated with traditional surgical techniques.…”
Section: Discussionmentioning
confidence: 99%
“…A minimally invasive technique for correcting vertical talus that relies primarily on serial casting was introduced almost ten years ago 17,18 . Multiple centers have reproduced the effectiveness of this technique in achieving initial correction (both radiographically and clinically), while maintaining excellent motion in the foot and ankle, for patients with both isolated and non-isolated vertical talus 10,[19][20][21][22][23][24][25][26] . In the present study, we compare the long-term outcomes of clinical and radiographic correction, foot function, and foot and ankle flexibility in patients with vertical talus (isolated and non-isolated) treated with either the minimally invasive method 17 or extensive soft-tissue release surgery.…”
mentioning
confidence: 99%
“…Nrf2 regulates the basal and inducible expression of antioxidant genes and other cytoprotective phase II detoxifying enzymes as key transcription factors (Eberhardt et al. 2012 ; Silva-Palacios et al. 2018 ; Chen Y et al.…”
Section: Antioxidant Effectmentioning
confidence: 99%